2014
DOI: 10.1371/journal.pone.0105596
|View full text |Cite
|
Sign up to set email alerts
|

Prognostic Impact of Renal Dysfunction Does Not Differ According to the Clinical Profiles of Patients: Insight from the Acute Decompensated Heart Failure Syndromes (ATTEND) Registry

Abstract: BackgroundRenal dysfunction associated with acute decompensated heart failure (ADHF) is associated with impaired outcomes. Its mechanism is attributed to renal arterial hypoperfusion or venous congestion, but its prognostic impact based on each of these clinical profiles requires elucidation.Methods and ResultsADHF syndromes registry subjects were evaluated (N = 4,321). Logistic regression modeling calculated adjusted odds ratios (OR) for in-hospital mortality for patients with and without renal dysfunction. R… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

2
5
0

Year Published

2015
2015
2022
2022

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 13 publications
(7 citation statements)
references
References 28 publications
(35 reference statements)
2
5
0
Order By: Relevance
“…This view is supported by previous studies performed in patients with HF. [14][15][16] Similar observations were also made in studies investigating the relationship between APE and GFR. [6][7][8] These studies suggest a significant correlation between GFR and various radiological and echocardiographic right ventricular functional parameters, since eGFR MDRD is significantly correlated with the RV-LV ratio, PAOI, and SVC diameter.…”
Section: Renal Dysfunctionsupporting
confidence: 75%
See 1 more Smart Citation
“…This view is supported by previous studies performed in patients with HF. [14][15][16] Similar observations were also made in studies investigating the relationship between APE and GFR. [6][7][8] These studies suggest a significant correlation between GFR and various radiological and echocardiographic right ventricular functional parameters, since eGFR MDRD is significantly correlated with the RV-LV ratio, PAOI, and SVC diameter.…”
Section: Renal Dysfunctionsupporting
confidence: 75%
“…However, increasing evidence suggests that increased CVP is what mainly determines renal function. [14][15][16] In addition, a number of neurohumoral mediators take part in the regulation of GFR. 17 Decreased GFR in APE can be explained by several mechanisms.…”
Section: Renal Dysfunctionmentioning
confidence: 99%
“…Renal 22 However, in the KorHF registry data, renal dysfunction (creatinine [Cr] level 2.0 mg/dL) is associated with poor clinical outcomes only in univariate analysis, but not in multivariate analysis. 9 The KorAHF registry showed that Cr level greater than or equal to 2.0 mg/dL at admission was one of the most important poor prognostic factors of in-hospital mortality and postdischarge mortality in multivariate regression analysis.…”
Section: Renal Dysfunctionmentioning
confidence: 99%
“…21 CKD confers a clinically significant risk for higher mortality in patients with CHF. [22][23][24] In this context CKD is also suspected to be a factor influencing the response to carvedilol therapy.…”
Section: Involvement Of Ckdmentioning
confidence: 99%